NARASI TOLERANSI BERAGAMA DI MEDIA SOSIAL: (STUDI ATAS AKUN TWITTER KOMUNITAS KATOLIK GARIS LUCU) - Arina Al-Ayya (Faculty of Cultures and Languages UIN Raden Mas Said, 2022)
Policies issued by the government and medical units to deal with the Covid-19 pandemic have somewhat affected people’s lives. One thing that is quite noticeable is the construction of communication on social media, which is increasingly being carried out by people globally. To build a ‘healthy climate’ on social media, the role of non-personal accounts in maintaining the integrity of religious tolerance is crucial. This article aimed to analyze the narrative of religious tolerance from the Twitter account of Komunitas Katolik Garis Lucu (@katolikG). Its existence as one of the accounts under the name of Garis Lucu (GL) indicates that they bring a spirit of peace in using social media. The current research described the existence of @katolikG’s account on social media and interpreted the messages concerning religious tolerance. The research used a qualitative approach with data collection based on a literature study. In presenting the data, the researcher utilized the descriptive-analytical method and employed the semiotic analysis of Roland Barthes to analyze the data. The results revealed that the Twitter account of @katolikG seeks to build religious tolerance on social media by creating messages within the scope of global multiculturalism. As its messages are wrapped in the form of jokes, memes, and satire, @katolikG builds religious discourse full of adaptability, flexibility, and tolerance in accepting differences.